PENGARUH KEUNGGULAN BERSAING, TEKNOLOGI DIGITAL DAN LITERASI KEUANGAN TERHADAP KINERJA UMKM: THE EFFECT OF COMPETITIVE ADVANTAGE, DIGITAL TECHNOLOGY AND FINANCIAL LITERACY ON MSMEsPERFORMANCE - Susilatri, Susilatri; Humairoh, Fitri; Ramaiyanti, Sinta; Azlina, Nur (Universitas Riau, 2024)
This study aims to analyze the effect of competitive advantage, digital technology and financial literacy on the performance of MSMEs in Bengkalis Regency. The analysis technique used is the mix method, with the aim of confirming the results of quantitative research. The method used is. The population in this study was 498 MSME actors registered with the Cooperatives and MSMEs Service of Bengkalis Regency. While the sample in this study amounted to 222 MSME actors determined using the Slovin formula. The data used is primary data, where respondents were given written questionnaires/questions and interviews with several MSME actors. The data was tested using multiple linear regression to determine the accuracy of the effect of competitive advantage, digital technology and financial literacy on the performance of MSMEs in Bengkalis Regency. The test results show that competitive advantage and digital technology have an effect on the performance of MSMEs. Meanwhile, financial literacy has no effect on the performance of MSMEs in Bengkalis Regency. The interview results also show the importance of competitive advantage and technology utilization in MSMEs.